If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = p + -15 Reorder the terms: -15 = -15 + p Add '15' to each side of the equation. -15 + 15 = -15 + 15 + p Combine like terms: -15 + 15 = 0 0 = -15 + 15 + p Combine like terms: -15 + 15 = 0 0 = 0 + p 0 = p Solving 0 = p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 0 + -1p = p + -1p Remove the zero: -1p = p + -1p Combine like terms: p + -1p = 0 -1p = 0 Divide each side by '-1'. p = 0 Simplifying p = 0
| 5(x-1)-3=1+3x | | mn-6n+3m-18=0 | | -15=-12+x | | =5x(-x+1) | | 7x/10+2=16 | | -15=-12+6 | | =(2x^2y)(-5x^4y^5) | | y+3y-1+5+y=180 | | 3x+17-5x=12-(6+3x) | | -14+x=-34 | | -7(9-6x)=3+9x | | b-18=-13 | | 21/(2+5)*12-8=x | | 5x-(4x+6)=-3 | | a-6=-1 | | a=-1 | | 2x+12-8x=19-x-5x | | -8=-7+r | | 2x-5+3x+85=180 | | 5x+3(50-x)=214 | | 3(x+3)=9x+4-6x+5 | | 9+v=7 | | -x=58 | | =(4c-1)(5c+3) | | 2a+7=3a-5 | | 102c=8.10 | | (7x^2+3)(3x^2-11x-4)=0 | | 2(y+6)=4(y-4) | | 2(y+6)=4(y-4) | | 6n-48=8n+16 | | 4(2k-6)=6(2k+2) | | 6v-24=10v-90 |